Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 1 - Section 1.5 - Inverse Functions and Logarithms - 1.5 Exercises: 15

Answer

$f^{-1}(17)=6$ $f(2)=3$

Work Step by Step

$\because f(6)=17, f^{-1}(f(6))=f^{-1}(17), f^{-1}(17)=6$ $\because f^{-1}(3)=2, f(f^{-1}(3))=f(2), f(2)=3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.